2008
DOI: 10.1038/npp.2008.22
|View full text |Cite
|
Sign up to set email alerts
|

Long-Interval Cortical Inhibition from the Dorsolateral Prefrontal Cortex: a TMS–EEG Study

Abstract: Several studies have demonstrated that cortical inhibition (CI) can be recorded by paired transcranial magnetic stimulation (TMS) of the motor cortex and recorded by surface electromyography (EMG). However, recording CI from other cortical regions that are more closely associated with the pathophysiology of some neurological and psychiatric disorders (eg, dorsolateral prefrontal cortex (DLPFC) in schizophrenia) was previously unattainable. This study, therefore, was designed to investigate whether CI could be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
200
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 215 publications
(214 citation statements)
references
References 41 publications
(67 reference statements)
13
200
1
Order By: Relevance
“…Using TMS-EEG, several studies have shown that LICI is associated with reduced excitability in both motor and nonmotor areas of cortex [23,[39][40][41]. For the primary motor cortex, the magnitude of this inhibition correlates with inhibition of the MEP, demonstrating the involvement of mechanisms comparable to those reflected by conventional LICI measurements.…”
Section: Mechanisms Of Licimentioning
confidence: 93%
See 2 more Smart Citations
“…Using TMS-EEG, several studies have shown that LICI is associated with reduced excitability in both motor and nonmotor areas of cortex [23,[39][40][41]. For the primary motor cortex, the magnitude of this inhibition correlates with inhibition of the MEP, demonstrating the involvement of mechanisms comparable to those reflected by conventional LICI measurements.…”
Section: Mechanisms Of Licimentioning
confidence: 93%
“…For all analyses, the TEP generated by test alone stimulation was compared to that generated following LICI 100 and LICI 150 . However, prior to quantification of paired-pulse TEPs, a correction procedure was carried out to remove the TEP generated by the conditioning stimulus from the TEP generated by the test stimulus [23,25,31]. This was achieved by time-shifting the TEP generated by test alone stimulation to coincide with the application of each conditioning stimulus, and subtracting it from the paired-pulse data (Fig 1; this was performed separately for LICI 100 and LICI 150 data).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Taken together with the finding that 20 Hz rTMS potentiates GABAergic inhibitory neurotransmission indexed through CSP (Daskalakis et al, 2006), we contend that high-frequency rTMS exerts its effects on g-oscillatory activity through GABA receptor-mediated inhibitory neurotransmission to ultimately affect WM performance. Future studies combining paired-pulse TMS with EEG recording to index GABA receptor-mediated neurotransmission in the DLPFC (Daskalakis et al, 2008) will be needed, however, to determine whether g-oscillatory activity is indeed potentiated directly through enhanced GABA.…”
Section: Discussionmentioning
confidence: 99%
“…Among patients with schizophrenia, several studies have demonstrated pervasive cortical inhibition deficits. For example, Daskalakis et al [41] reported pervasive GABA B deficits in the motor and DLPFC using TMS-EEG. In healthy cannabis users, Fitzgerald et al examined light versus heavy cannabis use in healthy controls, and reported reduced cortical inhibition regardless of cannabis use status [42].…”
Section: Neurophysiologymentioning
confidence: 99%